Phytohemagglutinin-induced activity of cyclic AMP (cAMP) response elements from cytomegalovirus is reduced by cyclosporine and synergistically enhanced by cAMP. - Niller, H H (1990)
The 19-base-pair enhancer repeat of the human cytomegalovirus immediate-early 1 gene mediates cyclic AMP- and phytohemagglutinin-induced expression in Jurkat T cells. Synergistic activity was observed in the presence of both drugs, suggesting a convergence of the protein kinase A and C pathways on this transcription element. In addition, the immunosuppressive drug cyclosporine strongly reduced the ability of the 19-base-pair repeat to activate gene expression in phytohemagglutinin-stimulated T cells.